PELAKSANAAN INFORMED CONSENT DI RUMAH SAKIT UMUM DAERAH Dr. ACHMAD MOCHTAR DALAM KAJIAN HUKUM PERJANJIAN - Sartika Sari; Nuzul Rahmayani; Kartika Dewi Irianto (Ensiklopedia of Journal, 2023)
This study aims to determine the Implementation of Informed Consent at the Regional General Hospital Dr. Achmad Mochtar in the Study of Agreement Law. What are the efforts of the hospital in explaining informed consent carried out by the hospital and what forms of implementation of informed consent are at the Regional General Hospital Dr. Achmad Muchtar between the hospital and the patient. This research includes descriptive empirical legal research using primary and secondary data types. In this study, the data collection techniques used by the authors were field studies and literature studies related to the problem under study. The agreement is an agreement between the two parties. Based on the results of the study, it can be seen that there are obstacles regarding the patient's or family's lack of understanding of the actions to be taken, causing difficulties for doctors to make decisions. It can be seen that the way to overcome this problem is that the doctor is required to provide an explanation of information in clear, simple, and easily understood language by various groups. Regarding the difficulties of patients or families with low levels of education and illiteracy in understanding, understanding, filling out, and signing informed consent. The way to overcome this is through doctors and paramedics who provide an explanation of the importance of the agreement, including assisting in writing and signing the informed consent. In terms of knowing how to implement informed consent at the Regional General Hospital.